Влияние ряда факторов на электронную структуру азида таллия - Суровой Э. П. Эдуард Павлович; Черников Е. В. Евгений Викторович; Грибанова Т. И. Татьяна Ивановна; Белялов А. Ш. Аскар Шингистаевич (1985, 1985)
Деп. в ОНИИТЭХим г. Черкассы 21.08.85, № 863-ХП-85.